2014
DOI: 10.1155/2014/680987
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, Molecular and Electronic Structure, Vibrational Spectroscopic Investigation, and Anti-HIV-1 Activity of Karanjin Using Density Functional Theory

Abstract: “Karanjin” (3-methoxy furano-2,3,7,8-flavone) is an anti-HIV drug, and it is particularly effective in the treatment of gastric problems. The method of isolation of “Karanjin” followed the Principles of Green Chemistry (eco-friendly and effortless method). The optimized geometry of the “Karanjin” molecule has been determined by the method of density functional theory (DFT). Using this optimized structure, we have calculated the infrared wavenumbers and compared them with the experimental data. The calculated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[11][12][13] These results motivated us to develop new species (possibly drugs) from favipiravir, perform comparative molecular docking, and reexamine their biological and pharmacological activities. As part of an ongoing study, [14][15][16][17] a comparative study of molecular docking, structure, electrons, and Fukui functional studies on favipiravir and its newly developed derivative of the COVID-19 protease (potential inhibitor) is conducted. As far as we know, comparative studies of these species are not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] These results motivated us to develop new species (possibly drugs) from favipiravir, perform comparative molecular docking, and reexamine their biological and pharmacological activities. As part of an ongoing study, [14][15][16][17] a comparative study of molecular docking, structure, electrons, and Fukui functional studies on favipiravir and its newly developed derivative of the COVID-19 protease (potential inhibitor) is conducted. As far as we know, comparative studies of these species are not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are known to exhibit strong antioxidant properties and are also one of the main components of many natural dyes making it very useful in pharmaceutical and textile industries [20]. One of such compounds is karanjin (3-methoxy furano-2,3,7,8flavone), a bioactive furanoflavonoid isolated from the seeds of Pongamia pinnata [21,22]. Keeping in view the importance of the detection of such flavonoids, the prepared Cu NPs have been used to increase the Raman intensity of karanjin through SERS.…”
Section: Introductionmentioning
confidence: 99%